Impact of Exogeneous Foliar Application of Micronutrients on Leaf Nutrient Status of Lemon [Citrus limon (L.) Burm.] cv. Assam Lemon - KH. Anush Sheikh (Journal of the Indian Society of Soil Science, 2023)
Lemon [Citrus limon (L.) Burm.] cv. Assam lemon is one of the most important species of citrus cultivated in warm southern slopes of the Himalayas in north-eastern India. Since this cultivar of lemon is having a prominent trait of bearing fruits in several flushes throughout the year. More precise management of nutrition is required to meet the nutrient demand of the crop for various physiological process in the plant system. In this experiment, a randomized block design having twelve treatments with three replications was followed to find out the influence of foliar application of micronutrients on leaf nutrient status of lemon during the year 2019. Among all, the treatment T12 [ZnSO4 (0.2%) + FeSO4 (0.2%) + Borax (0.2%) + CuSO4 (0.2%)] gave the best performance in improving the leaf nutrient status of lemon. The maximum content of total nitrogen (2.53%), total phosphorus (0.16%), zinc (37.6 µg g-1 ), iron (86.5 µg g-1 ), boron (41.2 µg g-1 ) and copper (27.1 µg g-1 ) were obtained which revealed that the leaf nutrient status of lemon depends on the application of different micronutrients.